Unveiling the dual anti-viral and anti-bacterial potential of Tridax procumbens: integrating system biology and molecular modeling for therapeutic insights - Muthanna Saadi Farhan; Farrah Rasool Jaafar; Amjad I. Oraibi (Pensoft Publishers, 2024)
This study evaluates the dual anti-viral and anti-bacterial activity of Tridax procumbens using system biology and molecular docking targeting the tumor necrosis factor (TNF) signaling pathway. The bioactive potential of Tridax procumbens was studied using phytochemical databases, and the essential biomolecules were selected for the study. The principle of geneVenn diagrams and protein target prediction was used to identify overlapping molecular targets with viral and bacterial diseases, which was later validated using various database mining tools like GeneCards and OMIM. Cytoscape software was applied to construct protein-protein interaction networks, which showed that TNF, AKT1, EGFR, SRC, and ESR1 are the hub genes of the networks. The gene ontology (GO) enrichment analysis also recapitulated the modulated biological processes, cellular components, and molecular functions of Tridax procumbens compounds, including their action on the TNF signaling in inflammation and immune responses. Molecular docking studies showed strong binding affinities of compounds such as cynaroside and 5,7,2,3,4-Pentahydroxy-3,6-dimethoxyflavone 7-glucoside to TNF, and molecular dynamics simulations confirmed these interactions' stability. The findings suggest that Tridax procumbens exerts its therapeutic effects by modulating the TNF signaling pathway, offering significant anti-viral and anti-bacterial properties. This integrative approach provides insights into the Tridax procumbens's mechanisms of action, supporting its potential as a source of novel therapeutic agents against infectious and bacterial diseases. There is still a need for further experimental research to define the full spectrum of Tridax procumbens' therapeutic application.